The Impact Of Debt Financing On Startup Profitability - Zhang, Chengzhuo (2023)
Due to the impact of the COVID-19 pandemic, the economic situation in Asia has become increasingly tense. As a result, some new companies have recently entered the market, which may prompt them to seek debt financing. In terms of economic impact, researching startups is considered positive because they bring changes in cash flows that contribute to the expansion of economic operations in the Asian region. Debt financing is one form of financing, and studying debt financing for start-ups aids in their growth. When a startup is allowed to take on debt, it is generally believed that the company will have a reasonable chance of achieving its operational goals and repaying the debt. This study utilizes the trade-off theory, signaling theory, and pecking order theory to examine the impact of debt financing on the profitability of start-ups. The research employs a regression analysis approach and selects companies listed on the National Equities Exchange and Quotation System (NEEQ) from 2020 to 2022. In the assessment, the study investigates the influence of debt financing on the profitability of startups. Finally, this study summarizes the research findings, highlights limitations, and provides prospects for future research. The study finds that the debt-to-assets ratio is negatively correlated with profitability, indicating that the debt level structure has an adverse impact on the profitability of start-ups.